AKTIVITAS BIOLOGIS MINYAK ATSIRI BIJI PALA PADA DAGING DAN PRODUK DAGING: REVIEW - Efilia Tri Wahyu Utami (JURNAL SAINS PETERNAKAN NUSANTARA, 2022)
Indonesia has a variety of spices that have the potential to be used as a fortifying agent for meat and meat products. This review aims to collect and summarize available evidence from publications that directly measure the biological activity of essential oils present in nutmeg used in meat and meat products. This study uses the literature study method, the literature criteria used are articles reporting on the biological activity of nutmeg essential oil used in meat and meat products published from 2012 to 2022. Nutmeg (Myristica fragrans) is a spice-containing oil. The essential oil which is widely used in the food industry. The most common essential oil constituents found in nutmeg are sabinene, pinene, limonene, terpineol, terpinene. Its components vary depending on changes in soil type, location, origin, method of extraction, and environmental conditions. The addition of nutmeg essential oil can slow down the oxidation of proteins and lipids in meat, control the growth of Escherichia coli and Enterobacter aerogenes, reduce the level of contamination of Salmonella typhimurium and be able to extend the shelf life of meat and meat products to a certain extent.. Keywords: Essential oil, nutmeg, biological activity, meat, meat product